Gambaran Escherichia Coli Pada Air Sumur Gali - Febry Risdhityatama Fahrurriza; Surati Surati (Jaringan Laboratorium Medis, 2020)
Most of the wells are still used as a source of drinking water. This well is widely used in the village of Rejosari Grobogan. Regulation of the Minister of Health No. 492 of 2010 concerning the Requirements for Quality of Drinking Water is 0 per 100 ml of sample. The existence of Escherichia coli in water sources affects water quality which has an impact on consumer health, so it is necessary to know whether the quality of water sources from dug wells meets drinking water standards. To find out whether Escherichia coli bacteria were present in the well water of Rejosari Grobogan Village. The research conducted included a type of quantitative research with a descriptive design. The sample used was 11 samples. The results of the examination showed that there was an Escherichia coli bacterium in the well water of Rejosari Grobogan Village with an average number of bacteria 1.8 per 100 ml of sample. Research on samples was carried out using the Most methodProbable Number (MPN). Rejosari Grobogan village water wells were found to contain Escherichia coli bacteria and not meet water quality standards in accordance with Minister of Health Regulation No. 32 of 2017.